2015
DOI: 10.1371/journal.pone.0127636
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Modulatory Effects of Bu-Zhong-Yi-Qi-Tang in Ovalbumin-Induced Murine Model of Allergic Asthma

Abstract: BackgroundBu-zhong-yi-qi-tang (BZYQT), an herbal formula of traditional Chinese medicine, has been an effective regimen of allergic diseases for nearly 800 years. Our previous report has demonstrated its anti-inflammatory effects in patients with perennial allergic rhinitis, and the aim of this study is to investigate the anti-asthmatic effect of BZYQT.MethodsFemale BALB/cByJNarl mice were sensitized with normal saline (control group) or OVA. Mice sensitized by OVA were fed with distilled water (OVA group), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Th1/Th2 balance is recognized as an important mediator of asthma; modulation of Th1/Th2 balance is thus considered beneficial for the treatment of asthma [2,14,15]. The present study revealed that after treatment with MXDT, increased levels of Th2 cytokines (IL-4 and IL-6) were downregulated, whereas decreased levels of the Th1 cytokine IFN-γ was upregulated, suggesting that MXDT can modulate Th1/Th2 balance.…”
Section: Discussionmentioning
confidence: 47%
“…Th1/Th2 balance is recognized as an important mediator of asthma; modulation of Th1/Th2 balance is thus considered beneficial for the treatment of asthma [2,14,15]. The present study revealed that after treatment with MXDT, increased levels of Th2 cytokines (IL-4 and IL-6) were downregulated, whereas decreased levels of the Th1 cytokine IFN-γ was upregulated, suggesting that MXDT can modulate Th1/Th2 balance.…”
Section: Discussionmentioning
confidence: 47%
“…Hochu-ekki-to has been reported to reduce complaints of general fatigue caused by common colds, and to improve severe weakness. Many studies have shown that it has various immunoactive effects, such as increasing immunity in elderly persons [6], augmenting natural killer cell activity [16], and increasing the production of cytokines [17]. In this study, the ACTH injection and coldstress groups both showed significant increases in their mRNA expression levels of glucocorticoid receptor (GR), IL-2, IL-4, and IFN-γ and concentrations of corticosterone, compared to the corresponding control groups (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…[ 20 ] It has been known as a herbal prescription for treating digestive disorders or conditions involving alternating cold and heat, such as malaria, for hundreds of years. [ 20 , 21 ] In recent research, anti-inflammatory and immunoregulatory effects of Bojungikki-tang have been revealed in animal experiments [ 22 , 23 ] and clinical trials. [ 24 , 25 ] These effects will also be beneficial for alleviating allergic symptoms.…”
Section: Discussionmentioning
confidence: 99%